Regional digital transformation strategies: algorithm for updating projects and goals - E. V. Lobkova; E. A. Osadchenko (Модернизация, инновация, развитие, 2023)
Purpose:   is to develop an approach to the procedure for updating regional strategic plans in the field of digital transformation, based on the algorithm for solving the problem of optimizing the levels of achievement of project goals in key industries of the constituent entities of the Russian Federation.Methods:  the research was based on the documents of the regulatory framework of strategic planning in the Russian Federation and the texts of approved and updated strategies of the constituent entities of the Russian Federation in the field of digital transformation. Methods of constructing strategic maps and decomposing goals, linear programming and finding the optimal solution were used.Results: the formulation of the linear programming problem has been detailed to find the optimal values for achieving the goals of digital transformation, taking into account the features of its field of application. The procedure for decomposing strategic goals and assigning coefficients of relationship between them is illustrated. The quantitative estimates obtained by the authors for solving the problem are presented and explained.Conclusions and Relevance:   in the process of developing and subsequent updating of strategic plans for digital transformation, the constituent entities of the Russian Federation are guided by the recommendations of federal authorities and territorial specifics. They take into account new trends in the digital transformation of industries, achievements and limitations on the path to fundamentally different conditions for managing the region and doing business. Digital transformation is proceeding with varying degrees of intensity – there is both territorial and industry differentiation. To a large extent, the speed of transformation processes depends on the ongoing regional policy and the content of the implemented strategic digital projects. The revision of the list of projects and target indicators is due to the necessary adjustment of the goals and emphasis of the transformation process. Assessing the optimal values of industry development indicators, taking into account resource limits, serves the purpose of updating regional strategic plans in the field of digital transformation of key industries and areas.